Critical discourse analysis and the semiotic construction of gender identities - Magalhães, Izabel (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2018)
This study examines textual and semiotic aspects of adverts according to critical discourse analysis. The focus of the study is the concept of gender identity. In adverts, different texts are appropriated in new ways explicitly as well as implicitly. Here texts work in a process of discourse technologisation. Both the feminine and the masculine are represented discursively in their heterogeneity: the feminine is represented as a commodified body; it is also frail and pathological. The masculine is linked with power, but with fashion too. Adverts position readers ideologically, so that they can define their gender identities as consumers.